1981
DOI: 10.1037/0022-0167.28.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Approaching supervision from a developmental perspective: The counselor complexity model.

Abstract: This article presents a developmental model of counselor supervision that conceptualizes the training process as a sequence of identifiable stages through which the trainee progresses. The progress of the supervisee is described from the entry level counselor through the advanced master counselor stage. Characteristics of supervisees at each of the four levels of the model are discussed as well as the appropriate supervision environments that encourage development to the next highest level. The supervisor skil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
501
2
25

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(555 citation statements)
references
References 8 publications
(14 reference statements)
27
501
2
25
Order By: Relevance
“…Heppner and Roehlke (1984) found that use of supervision in novice traditional therapists was defined by demanding direction and advice on technique. Stoltenberg and McNeill (1997) and 56.5% across IAPT services and did note that service level factors (such as the size of the service and the use of stepped-care) did influence patient outcomes. Indeed the present dataset had a 3-level structure (1: service, 2: PWP, 3: patient) and indicates that further therapist effects studies in IAPT services need to increase the sample size of services at level Therapist effects and PWPs 30 1 of any MLM to be able to isolate the effect of service.…”
Section: Discussionmentioning
confidence: 99%
“…Heppner and Roehlke (1984) found that use of supervision in novice traditional therapists was defined by demanding direction and advice on technique. Stoltenberg and McNeill (1997) and 56.5% across IAPT services and did note that service level factors (such as the size of the service and the use of stepped-care) did influence patient outcomes. Indeed the present dataset had a 3-level structure (1: service, 2: PWP, 3: patient) and indicates that further therapist effects studies in IAPT services need to increase the sample size of services at level Therapist effects and PWPs 30 1 of any MLM to be able to isolate the effect of service.…”
Section: Discussionmentioning
confidence: 99%
“…This would appear to be verified by a major text on clinical supervision, in which developmental models of professional development have "emerged as the zeitgeist" (Watkins, 1997, p. 610). To illustrate, Stoltenberg and McNeill's (1997) chapter in this textbook describes an "integrated developmental model" within which the supervisees' competence is expected to fluctuate, and where excess complexity shakes their confidence, leading to "confusion, despair, vacillation" (p. 190). But over time the supervisee is expected to build a stable professional identity, including developing their own style.…”
Section: Illustration 2: the Deskilling-development Patternmentioning
confidence: 99%
“…In supervision this is traditionally characterized by developmental stages, such as the supervisee's progression from "level 1" (featuring beginning competence, high anxiety and concreteness) to "level 3" (featuring competence and autonomy: Stoltenberg and McNeill, 1997). This developmental trajectory is a good example of the way that complex systems move, through a dialectic process, from steady states through dis-organization (destabilization and chaos) to re-organization (integration) at a higher level of complexity (Magnavita, 2006).…”
Section: Illustration 2: the Deskilling-development Patternmentioning
confidence: 99%
“…Given the emphasis placed on appearing competent, interns may more often hide clinical mistakes than negative reactions to the supervisor. Alternatively, perhaps, because of predoctoral interns' advanced training and experience, they may be more aware of their countertransference reactions and may withhold this type of vulnerability (e.g., Stoltenberg, 1981).Finally, we wanted to extend the literature on nondisclosures beyond what has been investigated before. Thus, for our fourth goal, we questioned whether there were factors that would have facilitated supervisee disclosure.…”
mentioning
confidence: 99%
“…Given the emphasis placed on appearing competent, interns may more often hide clinical mistakes than negative reactions to the supervisor. Alternatively, perhaps, because of predoctoral interns' advanced training and experience, they may be more aware of their countertransference reactions and may withhold this type of vulnerability (e.g., Stoltenberg, 1981).…”
mentioning
confidence: 99%